Positioning the battle for your mind - Ries, Al; Trout, Jack (Warner Book, Inc., 1986)
The concept that sparked a revolution in advertising is the principle that can revolutionize your life. With it, you can beat the competition and win the battle for recognition in an overcrowded, media-blitzed marketplace. You can position anything: product, politician, country, company, career. This is the book that show you: how to use Madison avenue techniques to win the war for your prospect's mind ; how to find and use the competition's weakest link and build your strategy around it ; how to reposition a strong competitor and create a weak spot ; how to use your present position to its best advantage ; how and how not to choose a name for your product ; why-and when-less is more ; how recent trends affect your positioning